Evaluación de los riesgos mecánicos en el montaje de torres en líneas de subtransmisión de la Empresa Eléctrica Ambato y propuesta de un instructivo de Seguridad Laboral. - Barrera Flores, Héctor Aníbal (2011)
This research develops a work safety instructions Empresa Electrica Ambato to reduce the number of accidents caused by mechanical hazards in the assembly of metal towers subtransmission lines to support electrical conductors with voltage levels of 69,000 volts. Both development and instructional structure took into account prevention a baseline of security breaches and the results of a qualitative risk analysis as a first qualitative and quantitative filter and second filter in the risk level, supported by the Technical Standards Prevention No: 330 for the application of simplified evaluation method of accidents, 809 for working at heights and OHSAS 18001 with regard to risk management. The final risk assessment considered the consequence and probability as a result of an investigation of risks to critical activities categorized. The sobering results of this study includes control measures to reduce the risks inherent in each activity mechanical assembly of towers with interlocking procedures under legislation and ASME B 30.5, 35.1-2 UNE-EN, CRF OHSAS 18001-2007 for EEASA.